The effects of additive solutions on the development of storage lesions in canine platelet concentrates stored at 4°C. Issue 5 (9th May 2022) - Ravicini, Sara; Haines, Jillian M.; Hwang, Julianne K.; Wardrop, K. Jane
Abstract: Objective: To assess platelet storage lesion development as evaluated by measurement of metabolic markers, platelet activation markers, and aggregometry, and determine the occurrence of bacterial growth in platelets stored in platelet additive solution (PAS) at 4°C for 7 days. Design: Prospective, ex vivo experimental controlled study. Setting: Research laboratory of a university veterinary teaching hospital. Animals: Ten units of canine platelet concentrate collected from blood bank donations. Interventions: Concentrates were aliquoted into 4 separate bags containing 100% plasma (control) or 30% plasma and 70% of a PAS (Plasma‐Lyte A, Isoplate, or InterSol). Samples were stored at 4°C without agitation. At days 0, 3, 5, and 7, samples were analyzed for platelet count, mean platelet volume, glucose, lactate, lactate dehydrogenase, Po 2, Pco 2, degree of swirling, aggregate formation, aggregation via light aggregometry, surface P‐selectin via flow cytometry, and bacterial contamination via culture. Measurements and Main Results: Development of storage lesions was minimal, demonstrated by maintenance of a mean pH > 7.2 and mean lactate values <6 mmol/L at day 7 in all solutions. Glucose utilization did not vary significantly between any of the solutions. No significant difference was found between plasma and PAS for Po 2 and Pco 2 . P‐selectin expression measured via flow cytometry showed a low platelet activation percent in all the solutions. InterSol had the lowest mean maximum percent aggregation ( P  < 0.001) and Isoplate the highest ( P  < 0.05). The mean maximum percent aggregation increased between day 0 and day 7 in all solutions. No bacterial growth was found in any of the solutions. Conclusions: Overall, PASs were comparable to plasma for the cold storage of platelets. Cold‐stored platelets showed minimal storage lesion development with no bacterial growth. Plasma‐, Plasma‐Lyte A‐, and Isoplate‐stored platelets maintained function for up to 7 days at 4°C.